Electronic discharge summaries in cross-border care in the European Union: How close are we to making it happen?. (June 2014) - Döring, N; Doupi, P; Glonti, K; Winkelmann, J; Warren, E; McKee, M; Knai, C
Introduction: The political drive for cross-border care within the European Union and an increasing focus on integrated care both have implications for electronic health records. The hospital discharge summary is a critical component of systems to ensure quality and continuity of care, and in a cross-border setting would particularly benefit from an electronic version. We have explored the extent to which European Union level policy and practice on electronic health records address issues pertinent to the development and implementation of electronic discharge summaries for patients treated outside their own country. Methods: We approached the topic by analysing data from two different sources: European Union policy documents on topics relevant to electronic health records and deliverables of European Union-funded electronic health record-focused research and development projects. Elements pertinent to different aspects of interoperability – legal, semantic and technical – were extracted from both sources and their content compared to assess the degree of consistency between policy and implementation targets. Results: We identified 25 policy documents and 14 European Union-funded projects. Our results show that European legislation is increasingly aligned with projects funded through European Union sources and substantial progress has been accomplished in achieving electronic communication across European health systems. Nevertheless, the achievement of a European level interoperable discharge summary is still a distant goal, while inadequate attention has been paid to the coordination of current discharge summary practices in Member States. Discussion: If the harmonized European Union patient summary is also to function as an electronic discharge summary, further specific steps are needed that address issues of both content and processes related to communication.